Keterbukaan Diri dalam Membangun Hubungan Persahabatan Diadik Laki-Laki dan Perempuan - Stefanie Stefanie (Ultimacomm: Jurnal Ilmu Komunikasi, 2016)
Friendship is one of human most precious relationship which is voluntary and built in the principle of being there for each other. To establish an intimate relationship, each has to know the other better so the impersonal relationship will turn to personal through some stages. This study seeks to explain how dyadic friendship between male and female can develop through openness, which will be assessed through the Social Penetration Theory. The research uses case study methods with qualitative approach and post-positivist paradigm. The data were gathered through observation, indepth interview and document study, and presented in a descriptive manner. The subjects of this study are three friendships between opposite gender. It can be concluded that the penetration in a dyadic friendship between male and female is developed through some stages, in which self disclosure play an important role in determining the depth and the width of the relationship. The relationship duration can not fully guarantee the quality of the relationship. This study also finds the different way of self disclosure depending on the sex and gender. interpersonal relation, interpersonal communication, social penetration, dyadic friendship, opposite gender friendship, self disclosure